2005
DOI: 10.1080/02533839.2005.9671038
|View full text |Cite
|
Sign up to set email alerts
|

Study of vibration and sound characteristics of a copper gong

Abstract: The gong, a Chinese traditional musical instrument, is generally made of copper in a circular shape. The finite element model of the gong is first constructed to perform theoretical modal analysis (TMA). So, the natural frequencies and corresponding mode shapes can be obtained. Experimental modal analysis (EMA) is also carried out. Results show that both natural frequencies and mode shapes match quite well between TMA and EMA. The radiated sound spectra of the gong are also measured and compared with the vibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…This analysis highlights the duplication of the asymmetric modes due to asymmetries in the geometry of the instrument. These results are consistent with the experimental modal analysis previously performed by Tsai et al 22 This modal analysis allows for the identification of the location of linear modes and is therefore necessary for the location of sensor and actuator.…”
Section: A Preliminary Modal Analysissupporting
confidence: 91%
“…This analysis highlights the duplication of the asymmetric modes due to asymmetries in the geometry of the instrument. These results are consistent with the experimental modal analysis previously performed by Tsai et al 22 This modal analysis allows for the identification of the location of linear modes and is therefore necessary for the location of sensor and actuator.…”
Section: A Preliminary Modal Analysissupporting
confidence: 91%
“…A novel approach, which proposed in this study is adding a tradational gong geometry as air cavity to matrix material. The model dimensions is taken from the literature [30]. It is expected that the incident sound wave energy transform into vibration, and heat energy thanks to gong air cavity.…”
Section: Resultsmentioning
confidence: 99%
“…The thickness of matrix material is represented as h_matrix, and it is set as 30 mm in all models. The gong shape air cavity is obtained from the literature [30] and all dimensions are shown in Table 4.…”
Section: Design and Optimizationmentioning
confidence: 99%
“…In order to obtain the expression in the physical space of the NNM described in Eq. (7), we replace the expression (5) in the nonlinear change of variables in Eq. (3).…”
Section: A Background On Nonlinear Modesmentioning
confidence: 99%
“…Fletcher 4 showed that the pitch glide phenomenon depends on the ratio between the thickness of the gong and the height of its central shell. Tsai et al 5 performed an experimental and numerical linear analysis of a daluo. Jossic et al 6 underlined the presence of internal resonances in the xiaoluo using modal active control.…”
Section: Introductionmentioning
confidence: 99%